Downregulation of interferon alpha but not gamma receptor expression in vivo in the acquired immunodeficiency syndrome - Lau, A S; Read, S E; Williams, B R (The Journal of clinical investigation, 1988)
Interferons (IFN) elicit antiviral and antineoplastic activities by binding to specific receptors on the cell surface. In evaluating the role of IFN as therapeutic agents in AIDS, we investigated the expression of IFN alpha and gamma receptors on peripheral blood mononuclear cells (PBM) from patients with AIDS, ARC, and heterosexual control subjects using radioiodinated IFN alpha 2 and IFN gamma. The binding characteristics of the 125I-IFN alpha and gamma to PBM were analyzed to determine receptor numbers and dissociation constants. PBM from controls expressed 498 +/- 247 IFN alpha receptor sites/cell (n = 17). However, eight patients with ARC and seven patients with AIDS had a mean number of IFN alpha receptor/cell of 286 +/- 235 (P less than 0.05) and 92 +/- 88 (P less than 0.001), respectively. This was consistent with elevated levels of serum acid-labile IFN alpha and cellular 2-5A synthetase activity in patients. Treatment of PBM from the AIDS patients with exogenous IFN alpha in vitro resulted in minimal 2-5A synthetase induction in comparison to controls. In contrast, the expression of IFN gamma receptors in ARC (n = 5) and AIDS (n = 4) patients remained normal. Thus the decrease in IFN alpha receptor expression and consequent hyporesponsiveness to IFN alpha raises the question of the usefulness of IFN alpha therapy in end-stage AIDS. The normal expression of IFN gamma receptors in AIDS patients suggests that IFN gamma may prove useful in attempts to provide immune reconstitution.